Implementation model of Occupational Hazards Prevention Management System on a dairy industry in Riobamba- Ecuador - Villacres Cevallos, Edison Patricio (2016)
In Ecuador there are high rates of accidents and occupational diseases, companies are required by current legislation to implement management systems in occupational safety and health, but there is not a methodology for its proper implementation and operation that will improve the effectiveness of preventive management in the Ecuadorian dairy sector The purpose of this research was to design a model to implement an Occupational Hazards Prevention Management System on a Dairy industry in Riobamba-Ecuador. To design the implementation model, it was taken as the basis of international standards ISO 14001, decision 584 of the Andean Instrument on Safety and Health at Work, resolution 957 and OHSAS 18001, Executive Order 2393, Resolution No. C.D. 513 of the Ecuadorian legal regulations applicable, mainly in productive sectors, labor and health, as well as international standards issued by the International Labour Organization. To implement the Occupational Health and Safety Management System, a modular scheme supported by instructional training activities in each module was applied. The deployment of each module is subject to information during the diagnosis made at the beginning of the implementation process. The successful implementation of the management system caused a positive impact on organizational performance of the company PRASOL (Dairy Santillan), as it pertains to the performance of safety and occupational health, improving their efficiency, work environments for workers and decrease the labor accident. So also it laid the foundation for obtaining certification in the Ministry of Labour and the Ecuadorian Social Security Institute.